Reasons for Drug Use among American Youth by Consumption Level, Gender, and Race/Ethnicity: 1976–2005 - Terry-McElrath, Yvonne M. (2009)
This study examined self-reported reasons for the use of nine substances among nationally representative samples of US high school seniors participating in the Monitoring the Future study from 1976 through 2005. In general, social/recreational reasons were the most commonly reported reasons for the use of most drugs. However, for psychotherapeutic drugs, coping with negative affect and physical needs reasons were most commonly mentioned. Results indicated that the proportion of students reporting various reasons has shifted significantly over time. Further, we found significant differences by gender and race/ethnicity in reported reasons for use. Prevention and intervention efforts must address the facts that (1) while social usage reasons do predominate, it is essential to consider coping and drug-effect reasons for use as well; and (2) there are appreciable differences by gender and race/ethnicity in reasons for drug use.